READING AUTHENTIC EFL TEXT USING VISUALIZATION AND ADVANCE ORGANIZERS IN A MULTIMEDIA LEARNING ENVIRONMENT - Tsuiping Chen; Huifen Lin (Language Learning and Technology, 2007)
The purpose of this experimental study was to compare the effects of different types of computer-generated visuals (static versus animated) and advance organizers (descriptive versus question) in enhancing comprehension and retention of a content-based lesson for learning English as a Foreign Language (EFL). Additionally, the study investigated the interactive effect of students’ existing reading proficiency level and the above-mentioned treatments on their reading comprehension achievement. Students from two EFL reading sections (N = 115) were tested on their reading proficiency and then randomly assigned to one of four computer-based instructional modules—static visual alone, animation alone, animation plus descriptive advance organizer, and animation plus question advance organizer. Once having interacted with their respective instructional materials, students then took four criterion tests immediately afterward and again four weeks later. The results showed that the animation group outperformed the static visual group in one of the four tests, and that animation embedded with a question advance organizer had a marginal effect among the four treatments in facilitating the acquisition of L2 reading comprehension both for the immediate and the delayed posttests.